1993–1996: US Copyright Reform and the WIPO Internet Treaties - Haggart, Blayne (Copyfight, 2014)
As the preceding chapter discussed, the central rule in US copyright policymaking since 1909 has been inter-industry consensus. There may be a bias towards the content industries in the resulting legislation, but each industryʹs interests have to be represented. No consensus, no legislation. Based purely on precedent, we would expect that digital-copyright reform in the area of TPMs and ISP liability would primarily address the concerns of the content industries and other large players, with exceptions for other groups depending on their political and economic clout. True to form, and despite an eventful detour to Geneva for the Internet treaties,